Simple detection of the 5S ribosomal RNA of Pneumocystis carinii using in situ hybridisation. Issue 9 (September 1996) - Kobayashi, M; Urata, T; Ikezoe, T; Hakoda, E; Uemura, Y; Sonobe, H; Ohtsuki, Y; Manabe, T; Miyagi, S; Miyoshi, I
Abstract : AIMS: To investigate the effectiveness of digoxigenin incorporated double stranded DNA probes produced by the polymerase chain reaction (PCR), for the detection of Pneumocystis carinii, using in situ hybridisation (ISH). METHODS: Formalin fixed, paraffin wax embedded sections of 26 human lung samples from 11 patients with P carinii pneumonia (PCP), and 15 with various types of fungal and viral pneumonia, were obtained during necropsy or transbronchial lung biopsy. Three additional PCP induced rat lung samples were also tested. PCR probes were prepared using the digoxigenin labelling mixture, and they were amplified from the DNA of a PCP induced rat lung after administration of dexamethasone, on the basis that 5S ribosomal RNA sequences are identical in human and rat P carinii. ISH was performed using this probe, and visualised using the digoxigenin nucleic acid detection kit. An immunohistochemical study using anti-human Pneumocystis monoclonal antibody was also carried out in parallel. RESULTS: ISH positively stained eight (of eight) lung necropsy specimens from patients with PCP, three (of three) transbronchial lung biopsy specimens from patients with PCP, and none of the three PCP induced rat lung specimens. In contrast, none of the specimens from patients with pneumonia caused by Aspergillus sp (n = 5), Candida sp (n = 4), Cryptococcus sp (n = 2), mucormycosis (n = 2), or cytomegalovirus (n = 2) were positive on ISH or immunohistochemistry. CONCLUSIONS: Using a digoxigenin labelled PCR probe for the entire 5S rRNA sequence in conjunction with conventional staining, ISH is highly reactive and specific for the diagnosis of PCP.